2015
DOI: 10.11622/smedj.2015119
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency

Abstract: Vitamin D deficiency is common among elderly patients in temperate countries, especially in early spring due to reduced cutaneous synthesis during the winter months, (1,2) and in housebound individuals (3) and medical inpatients.The prevalence of vitamin D deficiency is even higher in elderly patients with fragility fractures, ranging from 55%-91.6%. A recent local study in Singapore showed a vitamin D deficiency prevalence of 57.5% and vitamin D insufficiency of 34.5% in elderly patients admitted to hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
0
24
0
3
Order By: Relevance
“…, which has both full-and half-kink solutions [4], the full-kink has an internal mode (ω1 ≈ 1.645) [35] while the halfkink does not [36]. The possibility of power-law (as opposed to exponential) tails in higher-order field theories adds further complications.…”
Section: Linearization About a Kink (Internal Modes) And Linearizatiomentioning
confidence: 99%
See 2 more Smart Citations
“…, which has both full-and half-kink solutions [4], the full-kink has an internal mode (ω1 ≈ 1.645) [35] while the halfkink does not [36]. The possibility of power-law (as opposed to exponential) tails in higher-order field theories adds further complications.…”
Section: Linearization About a Kink (Internal Modes) And Linearizatiomentioning
confidence: 99%
“…The possibility of power-law (as opposed to exponential) tails in higher-order field theories adds further complications. The kink of the φ 8 model with two degenerate minima, specifically V (φ) = (φ 2 − a 2 ) 2 (φ 2 − b 2 ) with a = 4/5 and b = 1, is reported to possess three internal modes (ω1 ≈ 2.068, ω2 ≈ 3.192 and ω3 ≈ 3.689) [36], while kink solutions with power-law tails of other sextic and non-polynomial models possess only the zero mode [37].…”
Section: Linearization About a Kink (Internal Modes) And Linearizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Sir, Gani and How (1) presented an informative overview of vitamin D deficiency and valuable information on treatment and nutritional requirements. The article clearly supports the use of vitamin D supplementation to enhance skeletal health.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Vitamin D deficiency gains more and more attention because it not only leads to osteopenia, osteoporosis [5] and increased fall [6] and fracture risk [7], but also mounting evidence has implied its role as an emerging risk factor for a good variety of chronic diseases [8]. A series of observational studies reported that low circulating concentrations of 25(OH)D were associated with high risk for cardiovascular diseases [9], cerebrovascular disease [10], cancer [11], type 2 diabetes mellitus [12], cognitive impairment [13], depression [14], orthostatic hypotension [15], and even all-cause mortality [16].…”
Section: Introductionmentioning
confidence: 99%